HUBUNGAN MANAJEMEN SUPERVISI AKADEMIK DAN KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DENGAN KINERJA GURU DI SMTA PSKD JAKARTA DAN DEPOK - Said Hutagaol; Somuntul Rumapea (Jurnal Manajemen Pendidikan, 2013)
This study aims to determine the correlation between management ofacademic supervision, principal’s interpersonalcommunication with the teacher’s performance atPSKD Senior High School Jakarta and Depok, with the management ofacademic supervision as independent variable (X1), principal’s interpersonalcommunication (X2) and dependent variabel teacher’s performance (Y).This study was conducted in PSKD Senior High School Jakarta and Depok from February to March2013. The research method is used for correlational research method.Data collection techniques use a questionnaire with Likert scale which measures 1-5. This research is represented by 60 of PSKD Senior High School teachers Jakarta and Depok as respondents. The techniques used are a simple correlation analysis, multiple correlation and multiple regression at alpha significance level at 0.05.This study concluded that Hypothesis 1 shows a positive and significant relationship between management ofacademic supervision and teacher’s performance with a correlation coeficient of ry1 = 0,417. Hypothesis 2 shows a positive and significant relationship between principal’s interpersonalcommunication and teacher’s performance with a correlation coeficient of ry2 = 0,371. Hypothesis 3 shows a positive and significant relationship between management ofacademic supervision, principal’s interpersonalcommunication simultaneously and teacher’s performance with a correlation coeficient of ry12 = 0,433.From the research results it can be concluded that the teacher’s performance at PSKD Senior High School Jakarta and Depok can be enchanced by improving the management ofacademic supervision and the principal’s interpersonal communication.Keywords : Management of Supervision, Interpersonal Communication and Performance.